Mechanism of anti-cancer activity of curcumin on androgen-dependent and androgen-independent prostate cancer - Abd. Wahab, Nurul Azwa; Lajis, Nordin; Abas, Faridah; Othman, Iekhsan; Naidu, Rakesh (MDPI, 2020)
Prostate cancer (PCa) is a heterogeneous disease and ranked as the second leading cause of cancer-related deaths in males worldwide. The global burden of PCa keeps rising regardless of the emerging cutting-edge technologies for treatment and drug designation. There are a number of treatment options which are effectively treating localised and androgen-dependent PCa (ADPC) through hormonal and surgery treatments. However, over time, these cancerous cells progress to androgen-independent PCa (AIPC) which continuously grow despite hormone depletion. At this particular stage, androgen depletion therapy (ADT) is no longer effective as these cancerous cells are rendered hormone-insensitive and capable of growing in the absence of androgen. AIPC is a lethal type of disease which leads to poor prognosis and is a major contributor to PCa death rates. A natural product-derived compound, curcumin has been identified as a pleiotropic compound which capable of influencing and modulating a diverse range of molecular targets and signalling pathways in order to exhibit its medicinal properties. Due to such multi-targeted behaviour, its benefits are paramount in combating a wide range of diseases including inflammation and cancer disease. Curcumin exhibits anti-cancer properties by suppressing cancer cells growth and survival, inflammation, invasion, cell proliferation as well as possesses the ability to induce apoptosis in malignant cells. In this review, we investigate the mechanism of curcumin by modulating multiple signalling pathways such as androgen receptor (AR) signalling, activating protein-1 (AP-1), phosphatidylinositol 3-kinases/the serine/threonine kinase (PI3K/Akt/mTOR), wingless (Wnt)/ß-catenin signalling, and molecular targets including nuclear factor kappa-B (NF-κB), B-cell lymphoma 2 (Bcl-2) and cyclin D1 which are implicated in the development and progression of both types of PCa, ADPC and AIPC. In addition, the role of microRNAs and clinical trials on the anti-cancer effects of curcumin in PCa patients were also reviewed.